Genetic diversity of Galium cracoviense, G. oelandicum and G. sudeticum (Rubiaceae) - Elżbieta Cieślak; Zbigniew Szeląg (Acta Societatis Botanicorum Poloniae, 2011)
Galium sect. Leptogalium Lange in NE Europe is represented by few, local endemic species which occur in the area covered by the continental ice sheet in the Pleistocene period. They are: G. cracoviense Ehrend. in S Poland, G. oelandicum (Sterner & Hyl.) Ehrend. in SE Sweden and G. sudeticum Tausch in SW Poland and N Czech Republic. 55 individuals from five populations of these species were analysed using AFLP markers. A total of 193 AFLP bands were detected using three combinations of primers; out of them 159 proved polymorphic (82.4%). The lowest values of Shannon's index and Nei's gene diversity were noted for G. oelandicum and the highest ones for G. sudeticum. The results indicate a relatively high level of genetic variability in each of endemic species in spite of that the studied species occupy very small areas and are represented by a low number of populations. We conclude that additional, demographic and genetic studies are necessary to monitor potential decrease of populations' size resulting mainly from the mechanical destruction of plants and their habitats caused by intense tourism or other human activities (as agriculture, e.g. grazing).